2014 7th International Conference on Biomedical Engineering and Informatics 2014
DOI: 10.1109/bmei.2014.7002909
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent algorithm based on neural network for combinatorial optimization problems

Abstract: In this paper, we construct a Hopfield-type neural network to solve combinatorial optimization problems which is very important to medicine and biology. We applied the neural network to the four-coloring map problems to show that the neural network is capable of finding 100 percent optimal solution in a short time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…In a combinatorial optimization problem, there is a finite or limited number of solutions available in the solution space. Most of the combinatorial optimization problems are considered as a complicated problem [8]. Simulated Annealing (SA) is one of the computational intelligence approaches for providing meaningful and reasonable solutions for combinatorial optimization problems [9] [10] and can be utilized for feature extraction (example; for cybersecurity threat detection).…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
See 2 more Smart Citations
“…In a combinatorial optimization problem, there is a finite or limited number of solutions available in the solution space. Most of the combinatorial optimization problems are considered as a complicated problem [8]. Simulated Annealing (SA) is one of the computational intelligence approaches for providing meaningful and reasonable solutions for combinatorial optimization problems [9] [10] and can be utilized for feature extraction (example; for cybersecurity threat detection).…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
“…As per our literature survey, it is found that simulated annealing is usually not utilized as a classifier [11]. However, the SA method is explored a lot for searching optimal solutions to problems such as the travelling salesperson problem [12], color mapping problem [8], traffic routing management problem [13], and clustering of large sets of time series [14].…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with the large number of single index methods, there are only few literature using multi-indexes approaches to evaluate or rank mutual funds. These little literature can be divided into four typologies: operational research methods such as data envelopment analysis (Basso & Funari, 2001;Charnes et al, 1985;Gouveia et al, 2018); those based on principal component analysis (Pearson, 1901); those based on intelligent analysis such as neural network (Indro, 1999;Li & Qu, 2022) or genetic algorithm (Wang & Li, 2002); those based on multi-criteria decision making (MCDM) method such as simple scoring method, the ideal solution TOPSIS method (Alptekin, 2009;Chang et al, 2010), and other MCDM methods (Alimi et al, 2012;Lee et al, 2009). One of the advantages of these comprehensive methods is that various aspects of fund performance are considered, although many approaches may not easy to operate in practice.…”
Section: Introductionmentioning
confidence: 99%